1997
DOI: 10.1021/jp962343i
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Al2O3-Supported Manganese Oxides by Electron Spin Resonance and Diffuse Reflectance Spectroscopy

Abstract: Alumina-supported manganese oxides, used as catalysts for the selective catalytic reduction of NO, were characterized by combined electron spin resonance and diffuse reflectance spectroscopies. Upon impregnation of the acetate precursor solution, the [Mn(H 2 O) 6 ] 2+ complex interacts strongly with surface hydroxyls of the γ-Al 2 O 3 . Evidence was obtained that this anchoring reaction proceeds at a Mn/OH ) 1/2 ratio up to 4.5 wt % Mn loading, leading to a highly dispersed oxidic manganese layer. At higher lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(82 citation statements)
references
References 29 publications
4
75
1
1
Order By: Relevance
“…EXAFS and Raman spectroscopy coupled with complementary ab initio calculations suggested that the structure of the manganese in MnOx/c-Al 2 O 3 was likely a four coordinate mononuclear species [19]. ESR studies revealed that all the manganese is present as isolated species at low loading levels, while the fraction of the isolated Mn species decreased with increasing the Mn loadings [20]. These results are in good agreement with our finding obtained from XRD, Raman, and EXAFS studies and clarified the structures of manganese oxides on alumina support.…”
Section: Structure Of Alumina-supported Manganesementioning
confidence: 99%
“…EXAFS and Raman spectroscopy coupled with complementary ab initio calculations suggested that the structure of the manganese in MnOx/c-Al 2 O 3 was likely a four coordinate mononuclear species [19]. ESR studies revealed that all the manganese is present as isolated species at low loading levels, while the fraction of the isolated Mn species decreased with increasing the Mn loadings [20]. These results are in good agreement with our finding obtained from XRD, Raman, and EXAFS studies and clarified the structures of manganese oxides on alumina support.…”
Section: Structure Of Alumina-supported Manganesementioning
confidence: 99%
“…Since the growth takes place via the formation of these polygonal crystals it is hard to estimate a grain size for this system. EPR is able to detect paramagnetically isolated species and gives information about the coordination of isolated sites, therefore it can be used to detect Mn 2+ and Mn 4+ , whereas Mn 3+ is usually not detected due to complete splitting of energy levels (no ground-state degeneracy) [28,29]. Normally, it is expected that any electron paramagnetic (EPR) spectrum, coming from the transitions between the electronic magnetic states (|Ms> |Ms 1>), to split into 6 hyperfine components separated about 90-110 G from each other.…”
Section: Resultsmentioning
confidence: 99%
“…Los óxidos mixtos de Mn y Ti se prepararon por un méto-do de impregnación húmeda, partiendo de disoluciones acuosas de la sal precursora, Mn(CH 3 COO) 2 . 2H 2 O, conteniendo las cantidades requeridas de Mn para obtener los óxidos mixtos denotados como XMn-TiO 2 (con X = 0.5, 1.0, 1.5 y 2.0, fracciones de la monocapa teórica) y añadiendo posteriormente el soporte TiO 2 anatasa (Tioxide, 129 m 2 /g).…”
Section: Preparación De Las Muestrasunclassified